How does Alcoa Fastening Systems in Europe sustainably achieve the North American levels of return? - Pogson, Glen Richard (2013)
Air travel has become part of everyday life over the past 20 years and Alcoa Fastening Systems is an integral part in the development of how aircraft are joined together. This thesis has been written to explore and better understand the key drivers for the differences in profitability between the North American market and the European counterpart of Alcoa Fastening Systems Aerospace businesses. Using a mixed methodology and focusing on the developing area of Product Service Bundling, this paper will derive strategic recommendations to sustainability close the gap and continue to enhance the European performance and returns.